Peran Budaya Organisasi Dalam Meningkatkan Kepuasan Kerja Serta Dampaknya Terhadap Kinerja Karyawan Bank Indonesia - Nailin Nikmatul Maulidiyah (Universitas Pendidikan Nasional, 2020)
ABSTRACTThe purpose of this research was to determine the effect of organizational culture on employee performance and the role of job satisfaction as an intervening variable. This research used an explanatory research design. The population of this research were all employees of Bank Indonesia Jember Representative Office consisting of 69 organic and non organic employees. The type of data analysis of this research was path analysis. The result of this research showed that organizational culture (X) having a positive and significant effect on job satisfaction (Z) of 50,2%, organizational culture (X) having a positive and significant effect on performance (Y) of 29,2%, job satisfaction (Z) has a positive and significant effect on performance (Y) by 34,4%, organizational culture (X) has a positive and significant effect on performance (Y) through job satisfaction (Z) of 46,4%.